2018
DOI: 10.1111/jpr.12203
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Softener Fragrances Modulate the Impression Toward Female Faces and Frontal Brain Activity

Abstract: This study aimed to investigate the modulatory effect of olfactory cues on impression toward faces. Twelve Japanese university students participated in the experiment. Before the participants had arrived, the experimental room had been filled with one of three fragrances of fabric softener as the ambient odor, or with no odor. All participants were exposed to each of the four odor conditions on separate days. In the experimental room, participants viewed 20 photographs of Japanese female faces and evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Seven studies observed significant decreases in Δ[HbO2] in response to various odors, e.g., relaxing essential oil odors during a massage (Eto et al, 2015 , 2016 ), olive oil odor (Mitsukura et al, 2021 ), forest odor (Song et al, 2019 ), Hinoki oil (Ikei et al, 2015 ), rose and orange oil (Igarashi et al, 2014 ), and floral spray (Tanida et al, 2008 ). It is important to note that some studies observed no significant effect of odor on cerebral hemodynamics (Maharjan et al, 2018 ; Onuma and Sakai, 2018 ; Kaimal et al, 2021 ; Tomono et al, 2021 ). Two studies reported Δ[HbT] only (Fujii et al, 2007 ; Kokan et al, 2011 ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Seven studies observed significant decreases in Δ[HbO2] in response to various odors, e.g., relaxing essential oil odors during a massage (Eto et al, 2015 , 2016 ), olive oil odor (Mitsukura et al, 2021 ), forest odor (Song et al, 2019 ), Hinoki oil (Ikei et al, 2015 ), rose and orange oil (Igarashi et al, 2014 ), and floral spray (Tanida et al, 2008 ). It is important to note that some studies observed no significant effect of odor on cerebral hemodynamics (Maharjan et al, 2018 ; Onuma and Sakai, 2018 ; Kaimal et al, 2021 ; Tomono et al, 2021 ). Two studies reported Δ[HbT] only (Fujii et al, 2007 ; Kokan et al, 2011 ).…”
Section: Resultsmentioning
confidence: 96%
“…fresh flower petals, collected on the day of testing as a stimulus, allowing the odor to diffuse into the air within a pressure container. Five studies implemented odor delivery mechanisms aiming to diffuse odor into the environment around the participant, including below the participants nose with the use of a wearable odor tray (Onuma and Sakai, 2018 ; Song et al, 2019 ; Tomono and Tomono, 2020 ; Kaimal et al, 2021 ; Tomono et al, 2021 ). One of these studies, Tomono and Tomono ( 2020 ) expelled odor vapor via a airflow generator toward the participant, whilst also measuring odor concentration produced to check odor concentration consistency ( Figure 11d ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another fNIRS application with social psychology for forming impressions through olfactory stimuli appears in the research article by Onuma and Sakai () entitled “Fabric Softener Fragrances Modulate the Impression Toward Female Faces and Frontal Brain Activity.” They investigated the modulatory effect of olfactory cues on impressions toward faces and sought possible neural correlates for the impressions. They revealed that the fragrances enhanced a feminine impression for the faces in a face‐dependent manner.…”
mentioning
confidence: 99%